Visible Light Induced High Resolution and Swift 3D Printing System by Halogen Atom Transfer. Issue 3 (3rd October 2022) - Tomal, Wiktoria; Kiliclar, Huseyin Cem; Fiedor, Pawel; Ortyl, Joanna; Yagci, Yusuf
Abstract: 3D printing technology offers solutions for numerous needs in industry and the daily life of individuals. In recent years, most research efforts have focused on this technology as the market share has grown and requirements have become specified in their related fields. In this work, a novel visible light induced 3D printing system with high resolution and short printing time using dimanganese decacarbonyl (Mn2 (CO)10 ) in combination with organic halides is reported. The radicals formed through halogen abstraction by photochemically generated manganese pentacarbonyl from organic halides with high quantum efficiency initiate the polymerization of acrylic resins. The kinetics of the process using various halide‐containing molecules in the photoinitiaiting system are investigated with real‐time fourrier transform infrared spectroscopy and photo‐differential scanning calorimetry analyses, and the characteristics of 3D printouts are presented and compared with that of the commercial photoinitiator, 2, 4, 6‐trimethylbenzoyl)phosphine oxide without Mn2 (CO)10 . The results obtained confirm that the combination of Mn2 (CO)10 and structurally diverse organic halides is a class of promising 3D system for various applications. Abstract : A novel, fast‐paced, and high‐definition 3D‐digital light processing printing initiation system involving dimanganese decacarbonyl and organohalides is described. Broad range of benzylic bromides and α ‐halogenated ketones are investigated for printing initiation and compared with commonly applied photoinitiator diphenyl(2, 4, 6‐trimethylbenzoyl) phosphine oxide. Better print‐out resolutions and higher printing speeds are obtained by the offered system.